2021
DOI: 10.1111/jfpp.15203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antioxidant activity of some plant extracts (rosemary, sage, and savory, summer) on stability of moringa oil

Abstract: Recently, synthetic antioxidants such as Butylated hydroxy anisole (BHA), Butylated hydroxy toluene (BHT) were used to prevent oxidation in many foods including oil. Due to toxic effect of these chemicals, there is a need to use natural ingredients acting an antioxidants and to make food safer for humanity by protecting them against undesirable oxidation (Economou et al., 1991; Özcan & Akgül, 1995; Pokorny et al., 1997). The spices used in the World to process various foods for culinary purposes have attracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…It is regarded as a natural alternative to artificial antioxidants to minimize oxidative reactions and extend shelf life while offering a high degree of consumer acceptance [9]. Previous research has found that rosemary exhibits higher antioxidant activity in moringa oil at 60 • C compared with sage and savory summer extracts [10]. Similar results have been reported by other researchers [11][12][13].…”
Section: Introductionsupporting
confidence: 73%
“…It is regarded as a natural alternative to artificial antioxidants to minimize oxidative reactions and extend shelf life while offering a high degree of consumer acceptance [9]. Previous research has found that rosemary exhibits higher antioxidant activity in moringa oil at 60 • C compared with sage and savory summer extracts [10]. Similar results have been reported by other researchers [11][12][13].…”
Section: Introductionsupporting
confidence: 73%
“…Natural antioxidants consisting of polyphenol compounds have been the subjects of intensive investigation recently. Among plant extracts, rosemary ( Rosmarinus officinalis L.) extract (RE) is extensively used in industrial applications and exhibits better antioxidant capability than sage, thyme, BHT, BHA, and α‐tocopherol (Ghafoor et al, 2021; Samotyja & Malecka, 2010). The addition of commercial RE improves the oxidative stability of oils and fats, animal byproducts, nut butter, and bakery products (Bak et al, 2020; Ban et al, 2016; Dai & Liu, 2021; Xie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely acknowledged that RE presents an excellent protective effect in lipids, mostly vegetable oils, while insufficient literature can be found concerning poultry fats with different lipid profiles (Gamel & Kiritsakis, 1999; Ghafoor et al, 2021; Oancea et al, 2020; Samotyja & Malecka, 2010). Chicken fat has become a promising raw material as well as edible fat when occupying a vital place in the traditional food industry like cooking oil, poultry products, chicken (meat) powder, chicken essence, and other seasonings (Bak et al, 2020; Hać‐Szymańczuk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the use of these products can prevent the development of many diseases. Polyphenolic antioxidants are bioactive compounds that have a significant role in the production of functional foods, that is, food products with high nutritional and biological values (Ghafoor et al., 2021). They can be extracted from plant material using alcoholic solutions, wherein the extraction conditions should be optimized (Abdin et al., 2019).…”
Section: Introductionmentioning
confidence: 99%